Neonatal hypertrophic cardiomyopathy with dyspnoea as the first symptom: a case report - Li, Xiaoxia; Hong, Shu-Jun; Hong, Hui; Zhang, Zhi-Qun; Li, Jing (Frontiers in Pediatrics, 2023)
Neonatal hypertrophic cardiomyopathy (HCM) is an idiopathic disease characterised by myocardial hypertrophy with normal or small ventricular chambers, a systolic hyperdynamic state and diastolic dysfunction. The etiology, pathogenesis and clinical manifestations of HCM are diverse, and it is likely to progress to sudden cardiac death. The highly heterogeneous nature of this disease determines the difficulty of its diagnosis, and it is especially rare to report that can be diagnosed conclusively in the neonatal period. However, when it does occur, the younger the age of onset is, the higher the mortality rate and the worse the prognosis. The genetic variants and diagnostic timing can affect the life course of the patient. This case report describes a neonate with a family history of HCM who was diagnosed with hypertrophic non-obstructive cardiomyopathy by echocardiography shortly after birth. At 4 years of age, the patient presented with slow weight gain, feeding difficulties, tachypnoea and diaphoresis, and cardiac ultrasound findings suggesting progression to severe hypertrophic obstructive cardiomyopathy, with a high likelihood of arrhythmias, heart failure, pulmonary hypertension, syncope and even sudden death. Neonatal congenital hypertrophic cardiomyopathy is extremely rare and difficult to diagnose before the onset of symptoms. Echocardiography has a definite diagnostic value in hypertrophic cardiomyopathy and helps in early detection and treatment. At the time of clinical diagnosis, children with hypertrophic cardiomyopathy should be asked about their family history and, if necessary, a survey of family members should be conducted for the early detection of mildly ill patients and gene carriers to enable timely intervention and treatment, which remains the focus of our research and efforts.